Kuijieling-Containing Serum Regulates Th17 and Treg Cell Differentiation by Inhibiting STAT3 Signaling In Vitro. (25th August 2019) - Long, Yu; He, Yuqing; Jie, Fengming; Li, Sixin; Wu, Yanli; Li, Yanwu; Du, Qun
Abstract : Object . To investigate the effect of Kuijieling (KJL) on the balance between T helper 17 (Th17) and regulatory T (Treg) cells in peripheral blood mononuclear cells (PBMC) in vitro and explore the underlying mechanism. Materials and Methods . PBMCs isolated from rats were stimulated with transforming growth factor- β, interleukin (IL)-6, and IL-23 to induce the imbalance of Th17 and Treg cells and were treated with 10, 5, or 2.5% KJL-containing serum. The proportion of Th17 or Treg cells in CD4 + T cells was analyzed by flow cytometry, the concentrations of IL-17, IL-21, and IL-10 were assayed by ELISA, mRNA expressions of retinoic acid-related orphan receptor γ t (ROR γ t), forkhead box protein 3 (Foxp3), and signal transducer and activator of transcription 3 (STAT3) were quantified by PCR, and phosphorylated STAT3 (p-STAT3) was analyzed by flow cytometry. Results . KJL-containing serum decreased the proportion of Th17 cells and increased the proportion of Treg cells in CD4 + T cells, decreased the concentration of IL-17 and IL-21, enhanced the level of IL-10 in the cell culture supernatant, promoted the expression of Foxp3, and inhibited the levels of ROR γ t, STAT3, and p-STAT3. Conclusion . KJL suppresses the STAT3 pathway to remedy the imbalance between Th17 and Treg cells.